Destroy Athens : 1η Μπιενάλε της Αθήνας : Τεχνόπολις του δήμου Αθηναίων, 10 Σεπτεμβρίου-18 Νοεμβρίου 2007 - Ανδριωτάκης, Μανώλης (Biennial, 2007)
An eclipse of narratives is perceived by many. The reason usually given has to do with this age, a "relativist" or "administrative" age, in which great narratives might appear commonplace, false, or -what is worse- obsolete. And it is true that the fields of public discourse -politics, science, philosophy- largely appear to renounce them. We live in a world where, apparently, the great, the dark, the nebulous issues of existence are to an ever increasing degree objects of theoretical investigation.